Ultrahigh-strength and super-corrosion-resistant quaternary magnesium alloy and preparation method thereof

By using the main raw materials of Gd, Y, Ge and Mg and rotary forging processing technology, an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy was prepared, which solved the problem of difficulty in taking into account the strength and corrosion resistance of magnesium alloy, and achieved the comprehensive performance of high strength, corrosion resistance and high plasticity.

CN119800180APending Publication Date: 2025-04-11SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411997252.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing magnesium alloys are difficult to balance between strength and corrosion resistance, and it is difficult to meet the needs of high-performance structural materials such as aerospace.

Method used

Gd, Y, Ge and Mg are used as the main raw materials to reduce the average grain size of the alloy through the rotary forging processing process, and the formation of eutectic structure is suppressed by the introduction of Y and Gd elements, improving the room temperature mechanical properties, and improving the corrosion performance of the alloy by the introduction of Ge elements.

Benefits of technology

The prepared ultra-high strength ultra-corrosion resistant quaternary magnesium alloy has a tensile strength of more than 400MPa at room temperature, an elongation of more than 8%, and a corrosion rate of less than 0.20mm/y in 3.5 wt% NaCl solution, and has ultra-high strength, ultra-corrosion resistance and high plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800180A_ABST
    Figure CN119800180A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium alloys, and particularly discloses an ultrahigh-strength super-corrosion-resistant quaternary magnesium alloy and a preparation method thereof. The ultrahigh-strength super-corrosion-resistant quaternary magnesium alloy comprises the following components in percentage by mass: 6-10% of Gd, 2-5% of Y, 0.1-2% of Ge and the balance of Mg and inevitable impurities, and the average grain size is 10.5 microns. The preparation method comprises the following steps: high-flux melting, rotary swaging processing and tubular furnace heat treatment. The prepared quaternary magnesium alloy has the advantages of ultrahigh strength, ultrahigh corrosion resistance and high plasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesium alloys, and more specifically, to an ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloy is the lightest engineering metal structural material currently available. It has high specific strength, excellent electromagnetic shielding performance, good processability and excellent damping performance. It has shown great application prospects in the fields of transportation, electronic communications, and aerospace. The widespread application of magnesium alloys is of great significance for the manufacturing industry to achieve lightweight, energy saving and emission reduction. However, compared with other engineering metal materials, magnesium alloys have lower strength. At present, the strength of commercial magnesium alloys is generally lower than 400MPa, which is difficult to meet the needs of advanced industries such as aerospace for high-performance structural materials; in addition, magnesium alloys are susceptible to erosion by corrosive media, have poor corrosion resistance, and are easily affected by corrosion, resulting in material damage, which restricts its wider application in engineering. Generally speaking, the corrosion resistance and mechanical properties such as strength of magnesium alloys are difficult to be compatible. Therefore, having both ultra-high strength and corrosion resistance is a difficulty in the application of magnesium alloys.

[0003] Chinese invention patent CN113981286A discloses a corrosion-resistant high-strength plastic magnesium alloy and its preparation method. Through fine grain strengthening and the addition of trace rare earth elements cerium and samarium to regulate the morphology and distribution of the second phase, the tensile strength of the magnesium-aluminum-tin-calcium-manganese alloy can be no less than 301MPa, and the hydrogen evolution rate can be as low as 2.8mm / y. Chinese invention patent CN116623050A discloses a preparation method for a microalloyed high-corrosion-resistant Mg-Sn-Ge alloy material, which is composed of Mg-xSn-yGe, wherein 0.01wt.%≤x≤0.4wt.%, 0.01wt.%≤y≤0.5wt.%. The invention patent discloses that the addition of Ge can inhibit the cathode reaction during the alloy corrosion process, thereby improving the corrosion resistance of the magnesium alloy.

[0004] However, the magnesium alloys prepared by the above-mentioned prior art have poor corrosion resistance or ultimate strength and are still difficult to be widely used in advanced industries such as aerospace. Therefore, the field still needs to continue to develop magnesium alloys with super strength and super corrosion resistance and suitable for advanced industries such as aerospace. Summary of the invention

[0005] In order to further improve the strength and corrosion resistance of magnesium alloys, the present application provides an ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy and a preparation method thereof.

[0006] In the first aspect, the present application provides an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy, which adopts the following technical solution: An ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy comprises the following components by mass percentage: 6-10% Gd, 2-5% Y, 0.1-2% Ge, and the balance is Mg and unavoidable impurities; the average grain size of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is 10.5 microns. Preferably, the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy contains 7-9% by mass of Gd.

[0007] Preferably, the mass percentage of Gd is 7-9%.

[0008] Preferably, the mass percentage of Y is 2-4%.

[0009] Preferably, the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy comprises the following components by mass percentage: 7.82% Gd, 3.11% Y, 0.32% Ge, and the balance being Mg and unavoidable impurities.

[0010] The prepared ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy has a tensile strength of more than 400 MPa at room temperature, an elongation of more than 8%, and a corrosion rate of less than 0.20 mm / y in a 3.5wt% NaCl solution.

[0011] In a second aspect, the present application provides a method for preparing an ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy.

[0012] A method for preparing an ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy comprises the following steps: (1) In an inert atmosphere, pure magnesium, Mg-Gd, Mg-Y and Mg-Ge master alloy powders are divided into four loading barrels in a high-throughput batching device, and a program is set to automatically proportion the ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy in a material tray and mix the materials in a transition chamber; (2) placing the material tray into a high-throughput melting device under a protective atmosphere, and after the magnesium alloy is completely melted to form a melt, cooling the material tray under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, placing the magnesium alloy ingot into a rotary forging die for rotary forging; (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace for aging heat treatment, and then water quenched to obtain an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy. In (1), the inert atmosphere is high-purity argon gas, and the purity of the high-purity argon gas is ≥99.999%; the mixing material is turned over 10-15 times in the transition chamber.

[0013] In (2), the protective atmosphere is high-purity argon gas, and the purity of the high-purity argon gas is ≥99.999%; the melting temperature is 690-740°C; and the static cooling time is 120-180 minutes.

[0014] In (3), the total power of rotary forging is 30-50KW, the rotary forging speed is 700-1100r / min, and the rotary forging time is 60-120s.

[0015] In the above (4), the temperature of the aging heat treatment is 150-250°C and the time is 20-72h.

[0016] In summary, this application has the following beneficial effects: 1. This application uses Gd, Y, Ge and Mg as main raw materials and a rotary forging process to prepare an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy. The rotary forging process is used to reduce the average grain size of the alloy, and the formation of eutectic structure is inhibited by introducing Y and Gd elements to improve its room temperature mechanical properties. The Ge element is introduced as an element for densifying the corrosion surface film to achieve a synergistic improvement in the corrosion-mechanical effect of the alloy.

[0017] 2. The quaternary magnesium alloy prepared by the preparation method of the present application has ultra-high strength, ultra-corrosion resistance and high plasticity, with a tensile strength of more than 400 MPa at room temperature, an elongation of more than 8%, and a corrosion rate of less than 0.20 mm / y in a 3.5wt% NaCl solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : Scanning electron microscope image of the ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy prepared in Example 1 of the present application.

[0019] Figure 2 : Hydrogen evolution curve of the ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with embodiments.

[0021] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0022] Example 1 This embodiment provides an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy, the specific composition of which is shown in Table 1, in units of wt.%, and the remainder is Mg and unavoidable impurities.

[0023] Table 1. Composition of quaternary magnesium alloy of Example 1

[0024] The preparation method of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is as follows: (1) Under pure argon gas (purity ≥ 99.999%), pure magnesium, Mg-20Gd, Mg-30Y and Mg-10Ge master alloy powders were divided into 4 loading barrels in a high-throughput batching equipment, and the program was set to automatically mix the components in the material tray according to Table 1, and mix the materials in the transition chamber, and the mixing was turned over 10 times; (2) Under the protection of high-purity argon gas (purity ≥ 99.999%), the material tray is placed in a high-throughput melting equipment and melted at 720°C. After the magnesium alloy is completely melted to form a melt, it is allowed to stand and cool under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, the magnesium alloy ingot is placed in a rotary forging die for rotary forging. The total rotary forging power is 37 kW, the rotary forging speed is 980 r / min, and the rotary forging time is 90 s.

[0025] (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace and aged at 200°C for 48 hours. After water quenching, an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy is obtained.

[0026] Example 2 This embodiment provides an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy, the specific composition of which is shown in Table 2, in wt.%, and the remainder is Mg and unavoidable impurities.

[0027] Table 2. Composition of quaternary magnesium alloy of Example 2

[0028] The preparation method of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is as follows: (1) In an inert atmosphere of pure argon gas (purity ≥ 99.999%), pure magnesium, Mg-30Gd, Mg-30Y and Mg-20Ge master alloy powders were divided into 4 loading barrels in a high-throughput batching equipment, and the program was set to automatically mix the components in the material tray according to Table 2, and mix the materials in the transition chamber, and the mixing was turned over 12 times; (2) Under the protection of high-purity argon gas (purity ≥ 99.999%), the material tray is placed in a high-throughput melting equipment and melted at 690°C. After the magnesium alloy is completely melted to form a melt, it is allowed to stand and cool under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, the magnesium alloy ingot is placed in a rotary forging die for rotary forging. The total rotary forging power is 30 kW, the rotary forging speed is 700 r / min, and the rotary forging time is 120 s.

[0029] (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace and aged at 120°C for 72 hours. After water quenching, a quaternary magnesium alloy with ultra-high strength and ultra-corrosion resistance is obtained.

[0030] Example 3 This embodiment provides an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy, the specific composition of which is shown in Table 3, in wt.%, and the remainder is Mg and unavoidable impurities.

[0031] Table 3. Composition of quaternary magnesium alloy of Example 3

[0032] The preparation method of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is as follows: (1) In an inert atmosphere of pure argon gas (purity ≥ 99.999%), pure magnesium, Mg-10Gd, Mg-20Y and Mg-30Ge master alloy powders were divided into 4 loading barrels in a high-throughput batching equipment, and the program was set to automatically mix the components in the material tray according to Table 3, and mix the materials in the transition chamber, and the mixing turnover number was 15 times; (2) Under the protection of high-purity argon gas (purity ≥ 99.999%), the material tray is placed in a high-throughput melting equipment and melted at 740°C. After the magnesium alloy is completely melted to form a melt, it is allowed to stand and cool under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, the magnesium alloy ingot is placed in a rotary forging die for rotary forging. The total rotary forging power is 50 kW, the rotary forging speed is 1100 r / min, and the rotary forging time is 60 s.

[0033] (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace and aged at 250°C for 20 h. After water quenching, a quaternary magnesium alloy with ultra-high strength and ultra-corrosion resistance is obtained.

[0034] Comparative Example 1 This comparative example provides an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy, the specific composition of which is shown in Table 4, in wt.%, with the remainder being Mg and unavoidable impurities.

[0035] Table 4. Composition of quaternary magnesium alloy of Comparative Example 1

[0036] The preparation method of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is as follows: (1) In an inert atmosphere of pure argon gas (purity ≥ 99.999%), pure magnesium, Mg-20Gd, Mg-30Y and Mg-10Ge master alloy powders were divided into 4 loading barrels in a high-throughput batching equipment, and the program was set to automatically mix the components in the material tray according to Table 4, and mix the materials in the transition chamber, and the mixing was turned over 10 times; (2) Under the protection of high-purity argon gas (purity ≥ 99.999%), the material tray is placed in a high-throughput melting equipment and melted at 720°C. After the magnesium alloy is completely melted to form a melt, it is allowed to stand and cool under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, the magnesium alloy ingot is placed in a rotary forging die for rotary forging. The total rotary forging power is 37 kW, the rotary forging speed is 980 r / min, and the rotary forging time is 90 s.

[0037] (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace and aged at 200°C for 48 hours. After water quenching, a quaternary magnesium alloy with ultra-high strength and ultra-corrosion resistance is obtained.

[0038] Performance testing 1. Microstructure observation: The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy prepared in Example 1 was observed by electron backscatter diffraction under a scanning electron microscope. The results are as follows: Figure 1 shown.

[0039] from Figure 1 It can be seen that the ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy prepared in Example 1 has a smaller grain size, and the average grain size of the magnesium alloy is 10.5 microns. This is because during the rotary forging process, the magnesium alloy is subjected to strong deformation stress and deformation rate, which causes the grains to recrystallize and recrystallize out, thereby reducing the grain size. When the grain size becomes smaller, the number of grain boundaries acting as corrosion barriers increases, which can more effectively block the expansion of corrosion. At the same time, the deformation stress generated will also promote grain boundary migration and grain texture reorganization, which helps to eliminate the original grain defects and increase the strength of the grain boundaries. Magnesium alloys with smaller grain sizes have higher strength and greater dislocation density at grain boundaries, which will also lead to a weakening of the barrier effect of grain boundaries on dislocations, thereby promoting the activity of grain boundary sliding and increasing the plasticity of the alloy.

[0040] 2. Hydrogen evolution performance and mechanical properties test The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloys prepared in Examples 1-3 and Comparative Example 1 were immersed in a 3.5wt% NaCl solution at room temperature for 168h, and the immersion hydrogen evolution test was performed to calculate the hydrogen evolution rate. The tensile strength and elongation of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloys prepared in Examples 1-3 and Comparative Example 1 were tested. The results are shown in Tables 5 and Figure 2 shown.

[0041] Table 5. Performance test results

[0042] from Figure 2 It can be seen that the ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy prepared in Example 1 was immersed in a 3.5wt% NaCl solution for 168h at room temperature, and the amount of hydrogen evolution was only 0.42mL / cm 2 The hydrogen evolution rate is 0.06 mL / (cm 2·day); It can be seen from Table 5 that the ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy prepared in this application is immersed in a 3.5wt% NaCl solution at room temperature for 168h, and the hydrogen evolution rate is no more than 0.09mL / (cm 2 ·day), the corresponding hydrogen evolution corrosion rate is 0.188mm / y, which is about 2 / 3 of the corrosion rate of ultra-pure magnesium, and has super corrosion resistance; the tensile strength is higher than 400MPa, and the elongation is not less than 8.1%. It has super corrosion resistance and ultra-high strength and high plasticity. In comparative example 1, the Ge content is too high, and the solid solubility of Ge in magnesium is almost 0, so too much second phase will be precipitated, and the galvanic corrosion area between the magnesium matrix will increase, and a large number of local corrosion areas will appear, and the corrosion will continue to intensify. Under room temperature, it is immersed in 3.5wt% NaCl solution for 168h, and the hydrogen evolution rate is 0.53mL / (cm 2 ·day), and the corresponding hydrogen evolution corrosion rate is 1.107mm / y.

[0043] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection required by the present application.

Claims

1. An ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy, characterized in that: The alloy comprises the following components by mass percentage: 6-10% of Gd, 2-5% of Y, 0.1-2% of Ge, and the balance of Mg and inevitable impurities; the average grain size of the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy is 10.5 microns.

2. The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 1, characterized in that: The mass percentage of Gd is 7-9%.

3. The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 2, characterized in that: The mass percentage of Y is 2-4%.

4. The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 3, characterized in that: The composition is as follows by mass percentage: 7.82% of Gd, 3.11% of Y, 0.32% of Ge, and the balance is Mg and inevitable impurities.

5. The ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 4, characterized in that: The ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy has a tensile strength of more than 400 MPa at room temperature, an elongation of more than 8%, and a corrosion rate of less than 0.20 mm / y in a 3.5wt% NaCl solution.

6. A method for preparing the ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) In an inert atmosphere, pure magnesium, Mg-Gd, Mg-Y and Mg-Ge master alloy powders are divided into four loading barrels in a high-throughput batching device, and a program is set to automatically proportion the ultra-high-strength and ultra-corrosion-resistant quaternary magnesium alloy in a material tray and mix the materials in a transition chamber; (2) Under a protective atmosphere, placing the material tray in a high-throughput melting device for melting, and after the magnesium alloy is completely melted to form a melt, standing and cooling under a protective atmosphere to obtain a magnesium alloy ingot; (3) At room temperature, placing the magnesium alloy ingot into a rotary forging die for rotary forging; (4) The magnesium alloy ingot after rotary forging is placed in a tubular furnace for aging heat treatment, and then water quenched to obtain an ultra-high strength and ultra-corrosion-resistant quaternary magnesium alloy.

7. The method for preparing an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 6, characterized in that: In the above (1), the inert atmosphere is high-purity argon gas, and the purity of the high-purity argon gas is ≥99.999%; the number of times the mixed material is turned in the transition chamber is 10-15 times.

8. The method for preparing an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 7, characterized in that: In (2), the protective atmosphere is high-purity argon gas, and the purity of the high-purity argon gas is ≥99.999%; the melting temperature is 690-740°C; and the static cooling time is 120-180 minutes.

9. The method for preparing an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 8, characterized in that: In (3), the total power of rotary forging is 30-50KW, the rotary forging speed is 700-1100r / min, and the rotary forging time is 60-120s.

10. The method for preparing an ultra-high strength and ultra-corrosion resistant quaternary magnesium alloy according to claim 9, characterized in that: In the above (4), the temperature of the aging heat treatment is 150-250°C and the time is 20-72h.

Citation Information

Patent Citations

  • Corrosion-resistant high-strength plastic magnesium alloy and preparation method thereof

    CN113981286A

  • Microalloyed high-corrosion-resistance Mg-Sn-Ge alloy material and preparation method thereof

    CN116623050A